A Democratic ASEAN: Intergovernmentalism and Thin Democracy - Jones, William J (Thammasat Review, 2025)
The ASEAN Charter of 2007 upgraded the status of ASEAN from an informal organization of Cold War origins to a legally recognized regional organization that would in theory produce binding and credible agreements. The ASEAN Charter created the ASEAN Communities architecture in the image, but not the substance of the European Union. In this context, ASEAN affirmed in its legally binding treaty to uphold new normative understandings of human rights, rule of law, and democracy. This paper will conceptualize, problematize, and analyze the rhetoric to reality of an ASEAN as a democratic regional organization. The article demonstrates that current frameworks of a democratic ASEAN are misunderstood due to an analytical misalignment of units/levels of analysis. Lastly, the article argues that ASEAN is a democratic regional organization from a ‘thin’ definition and understanding of democracy.